Strategy for Developing Teaching Materials for Islamic Education Media and Technology Courses in the Digital Era - Aniza Fitri; Fathorrahman, Fathorrahman (Penerbit Hellow Pustaka, 2026)
In the digital era, technological advancements have transformed various aspects of life, including the field of education. Islamic Religious Education (PAI), as one of the academic disciplines taught in universities, is also required to adapt to the changing times—particularly in the development of more interactive, innovative, and technology-based teaching materials. The issue addressed in this study is how teaching material development strategies are implemented in the digital era within the Islamic education study program. This is elaborated through two main focuses: What are the strategies for developing teaching materials for the course